PENGGUNAAN READING INFUSION SQ3R MEREMEDIASI MISKONSEPSI PESERTA DIDIK PADA MATERI HUKUM ARCHIMEDES DI SMP - Sarniti, Eka; Sahala S, Stepanus; Oktavianty, Erwina (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aimed to remediate misconceptions learners Junior High School eighth grade 3 Sungai Raya on material using the Archimedes law reading infusion SQ3R can reduce misconceptions learners. The method used is pre experimental design with one group pretest post test design. Data taken from the students of class IX B selected intact group. The sample was 32 students. Data collection tool in the form of 18 multiple choice questions with three alternative answers and the reasons open. Based on the analysis of data obtained by the percentage reduction in the average number of students who have misconceptions of 65.48%. The average percentage decrease in the number of misconceptions of each concept by 68.50%. Based on McNemar test calculations obtained an average ?2Compute (13.33) ??2Table (3.84) for db = 1 and ? = 5%, then the overall conception significant changes after remediated using reading infusion SQ3R. DQM effectiveness calculations obtained 66.36 (medium category), the remediation using reading infusion SQ3R effective in addressing misconceptions learners. Keywords: Remediation, misconceptions, reading infusion, Archimedes law